Importance and peculiarities of investment policy in the formation of the investment climate for taxpayers - Tahirov Shuhrat Niyaz oglu (Zien Journals, 2022)
The main objectives of public structural investment policy; the investment environment is this; regional investment policy; The main objectives of the strategy are identified in three areas.
Keywords: Investment; Credit System; Tax; Finance